High-grain feeding causes strong shifts in ruminal epithelial bacterial community and expression of Toll-like receptor genes in goats - Liu, Jun-hua; Bian, Gao-rui; Zhu, Wei-yun; Mao, Sheng-yong (Frontiers in Microbiology, 2015)
High-grain (HG) feeding used in intensive goat production can affect the physiology of the rumen wall, but the changes induced in the epimural bacterial community and host Toll-like receptors (TLRs) are not well understood. In this study, ten male goats were randomly allocated to two groups and fed either a hay diet (0% grain; n=5) or an HG diet (65% grain; n=5). The changes in the ruminal epithelial bacterial community and expression of TLRs during long-term (seven weeks) HG feeding were determined using pyrosequencing and quantitative real-time polymerase chain reaction. Principal coordinate analysis and analysis of molecular variance results showed that HG feeding caused a strong shift in bacterial composition and structure. At the genus level, our data revealed that it increased the relative abundance of taxa Butyrivibrio, unclassified Clostridiales, Mogibacterium, unclassified Anaerolineaceae, and Succiniclasticum, and decreased the proportion of unclassified Ruminococcaceae, unclassified Rikenellaceae, unclassified Erysipelotrichaceae, Howardella, and unclassified Neisseriaceae. The HG-fed goats also exhibited upregulation of the relative mRNA expression of TLR2, TLR3, and TLR5 in the rumen epithelium (P<0.05). Correlation analysis revealed that the increase in TLR expression was associated with changes in the relative abundance of ruminal epithelial bacteria. This study provides a first insight into the adaptive response of ruminal epithelial bacterial populations to HG feeding in goats and shows that these changes were associated with alterations in TLR expression. These findings provide new insight into understanding of host–microbial relationships in ruminants.